How might we build limbs in vitro informed by the modular aspects and tissue-dependency in limb development? - Tsutsumi, Rio; Eiraku, Mototsugu (Frontiers in Cell and Developmental Biology, 2023)
Building limb morphogenesis in vitro would substantially open up avenues for research and applications of appendage development. Recently, advances in stem cell engineering to differentiate desired cell types and produce multicellular structures in vitro have enabled the derivation of limb-like tissues from pluripotent stem cells. However, in vitro recapitulation of limb morphogenesis is yet to be achieved. To formulate a method of building limbs in vitro, it is critically important to understand developmental mechanisms, especially the modularity and the dependency of limb development on the external tissues, as those would help us to postulate what can be self-organized and what needs to be externally manipulated when reconstructing limb development in vitro. Although limbs are formed on the designated limb field on the flank of embryo in the normal developmental context, limbs can also be regenerated on the amputated stump in some animals and experimentally induced at ectopic locations, which highlights the modular aspects of limb morphogenesis. The forelimb-hindlimb identity and the dorsal-ventral, proximal-distal, and anterior-posterior axes are initially instructed by the body axis of the embryo, and maintained in the limb domain once established. In contrast, the aspects of dependency on the external tissues are especially underscored by the contribution of incoming tissues, such as muscles, blood vessels, and peripheral nerves, to developing limbs. Together, those developmental mechanisms explain how limb-like tissues could be derived from pluripotent stem cells. Prospectively, the higher complexity of limb morphologies is expected to be recapitulated by introducing the morphogen gradient and the incoming tissues in the culture environment. Those technological developments would dramatically enhance experimental accessibility and manipulability for elucidating the mechanisms of limb morphogenesis and interspecies differences. Furthermore, if human limb development can be modeled, drug development would be benefited by in vitro assessment of prenatal toxicity on congenital limb deficiencies. Ultimately, we might even create a future in which the lost appendage would be recovered by transplanting artificially grown human limbs.